Kajian Teoritas Pengaruh Harga dan Kualitas Produk Terhadap Loyalitas Konsumen pada Bisnis Kuliner Digital - Maatuil, Rexy Andalangi; Markus, Jennifer; Anthe, Miquele E. O.; Manoppo, Marchelina A. P.; A. Sagay, Gainfasi; Gabriela Lumi (Indo Publishing, 2025)
The rapid expansion of digital culinary businesses has been driven by the increasing use of app-based food delivery platforms. Intense competition requires business owners to understand the key factors influencing consumer behavior, particularly customer loyalty. This study aims to analyze the influence of price and product quality on consumer loyalty in digital culinary businesses through a literature review of relevant scientific articles and books published within the last ten years. The findings indicate that fair, transparent, and competitive pricing significantly shapes repeat purchase decisions. Additionally, consistent product quality that meets expectations and ensures hygiene plays a major role in maintaining consumer trust. The reviewed literature also highlights that both variables simultaneously affect loyalty, with product quality often emerging as the more dominant factor compared to price. The uniqueness of this study lies in its focus on consumer behavior within digital food ecosystems, where ratings, reviews, and app-based service experiences strongly influence purchasing decisions. This study provides valuable implications for digital culinary MSMEs to optimize pricing strategies and improve product quality to sustain consumer loyalty in an increasingly competitive digital marketplace.